PENDIDIKAN SEKS ANAK USIA DINI: STUDI BERDASARKAN PENGALAMAN ORANG TUA - Kurniawati, Rafidhah; Taufik, Taufik (JURNAL KESEHATAN REPRODUKSI, 2024)
Background: Limited parental awareness regarding early childhood sex education contributes to the rising prevalence of sexual violence against children. Inadequate understanding of intimate boundaries and insufficient parental guidance place children at higher risk.Objective: To explore parental roles and the strategies employed in introducing and teaching sex education to early-aged children.Method: This research utilizes a qualitative design with a phenomenological approach. Data were obtained through unstructured interviews guided by interview prompts, involving six parents of children aged 2–6 years selected through purposive sampling.Results and Discussion: Findings indicate that parents view essential knowledge about intimate areas, gender distinctions, and modesty as foundational before educating children. Parents act as primary information providers, behavior regulators, communication partners, and interpreters of religious values in delivering sex education. Early sex education fostered responsibility and independence in maintaining personal hygiene and safety of intimate organs. Social support—originating from spouses, family members, teachers, peers, and the children themselves—strengthened parents’ capacity to optimize sex education practices.Conclusion: Parents hold a pivotal role as the initial source of information and behavioral guidance in early sex education. Adequate parental literacy, supported by social reinforcement, promotes children’s responsibility and autonomy in safeguarding their intimate areas.